PENGEMBANGAN MODEL PEMBELAJARAN TERINTEGRASI SOFT SKILL DAN HARD SKILL DALAM MENINGKATKAN KOMPETENSI WARGA BELAJAR PADA LEMBAGA KURSUS KECANTIKAN - Wiwin Herwina; H. Ajid Madjid (Jurnal Ilmiah Visi, 2018)
The research is based on the problem of how the initial condition of learning in the beauty course Institute, how the conceptual model of integrated learning soft skill and hard skills, how the implementation of integrated learning models soft skill and hard skill, how the effectiveness of the integrated learning model soft skill and hard skill that can improve the competence residents learn. The purpose of research to find the learning model integrated soft skill and hard skill in improving competence of studying citizen who conducted at LKP Yuwita city of Tasikmalaya in 2017. Research method used is description and experiment method. The sample for this research consists of one-person manager, two-person instructor, 20 people studying citizen. The results from the study showed (1) the initial condition of learning in the beauty course Institute, still dominated by the tutor. The residents were less involved in the learning, (2) expert validation has resulted in the integrated learning model in improving the competence of studying citizens, (3) learning of integrated soft skill and hard skill to improve the competence of studying citizens, and (4) integrated learning model of soft skill and hard skill developed for this research according to the result of qualitative and quantitative analysis from the test results has effectively increased the competence of studying citizen at the beauty course Institute. The conclusion from this research is that the integrated learning model of soft skill and hard skill developed has been effective in improving the competence of studying citizens at the beauty course Institute. References Anwar, S. (2004). Pendidikan kecakapan hidup (life skills education). Bandung: Alfabeta. Delors, J. (1996). Learning: The treasure within, report to UNESCO of the international commision on education for the twenty-first century. Paris: UNESCO Publishing. Depdiknas. (2007). Konsep dan strategi pengembangan pusat kegiatan belajar masyarakat (PKBM). Jakarta: Depdiknas. Gall, M.D., Gall, J.P., & Borg, W.R. (2003). Educational research: An introduction. New York: Ally and Bacon. Hamalik. (1986). Proses belajar mengajar. Jakarta: PT Bumi Aksara. Joesoef. (1986). Konsep dasar pendidikan luar sekolah. Surabaya: Bumi Aksara. Kamil, M. (2010). Model pendidikan dan pelatihan (Konsep dan aplikasi). Bandung: Alfabeta. Mulyasa. (2006). Kurikulum yang disempurnakan. Bandung: Remaja Rosdakarya. Prabowo. (2000). Pembelajaran terpadu di sekolah dasar. Unesa: LPM Unesa Syah. Rusyan, dkk. (1994). Pendekatan dalam proses belajar mengajar. Bandung: Remaja Rosdakarya. Saud, U.S. (2006). Perencanaan pendidikan suatu pendekatan komprehensif. Bandung: Rosdakarya. Sihombing. (2000). Pendidikan luar sekolah, managemen strategi: Konsep, kiat dan pelaksanaan. Jakarta: PD. Mahkota. Sudjana, N. (1987). Dasar-dasar proses belajar mengajar. Bandung: Sinar Baru Offset. Sudjana, N. & Ibrahim (2001). Penelitian dan penilaian pendidikan. Bandung: Sinar Baru Algesindo. Syah, M. (1995). Psikologi pendidikan dengan pendekatan baru. Bandung: PT Remaja Rosda Karya. Trisnahada.(2011). Pengembangan strategi penanaman nilai-nilai kejujuran dalam upaya membina disiplin dan kemandirian siswa melalui pembelajaran IPA di sekolah (studi pada MTs Negeri di Kabupaten Sumedang yang telah mengembangkan integrasi IPTEK dan IMTAQ). Disertasi. Bandung: Universitas Pendidikan Indonesia.